2010
DOI: 10.1002/mnfr.200900172
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary polyphenols on human platelet function – A critical review of controlled dietary intervention studies

Abstract: Cardiovascular disease is a chronic disease influenced by many factors, with activated blood platelets being one of them. Platelets play a central role in the formation of plaques within blood vessels, contributing to early inflammatory events. Consumption of diets rich in plant-based products protects against the development of cardiovascular disease. Polyphenols, which are secondary plant metabolites found in a wide range of foodstuffs and beverages, may be partially responsible for these effects. Their prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 85 publications
3
79
0
Order By: Relevance
“…The physiological relevance of the beneficial effects on platelets of an exposure to flavanols from cocoa consumption (equivalent to 100 g of dark chocolate with 70% cocoa solids) has been estimated to be comparable to standard doses of aspirin (~80 mg) clinically used as antiaggregant therapy [Pearson et al 2002]. However, chronic intake of polyphenols from berries (whole fruits or juices) may result in only a relatively low inhibition of platelet aggregation under shear stress [Ostertag et al 2010]. Other fruit juices such as orange juice, grapefruit juice and sea buckthorn juice taken daily for 7-10 days in healthy volunteers failed to reduce ex vivo platelet activity [Eccleston et al 2002;Keevil et al 2000].…”
Section: Platelet Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological relevance of the beneficial effects on platelets of an exposure to flavanols from cocoa consumption (equivalent to 100 g of dark chocolate with 70% cocoa solids) has been estimated to be comparable to standard doses of aspirin (~80 mg) clinically used as antiaggregant therapy [Pearson et al 2002]. However, chronic intake of polyphenols from berries (whole fruits or juices) may result in only a relatively low inhibition of platelet aggregation under shear stress [Ostertag et al 2010]. Other fruit juices such as orange juice, grapefruit juice and sea buckthorn juice taken daily for 7-10 days in healthy volunteers failed to reduce ex vivo platelet activity [Eccleston et al 2002;Keevil et al 2000].…”
Section: Platelet Functionmentioning
confidence: 99%
“…In parallel, the promotion of dietary therapies providing consistent inhibition of platelet function could be of interest. Based on epidemiological studies suggesting that diets rich in flavonoids can reduce the risk of arterial thrombosis [Arts and Hollman, 2005], it seems interesting to investigate the ability of these bioactives to inhibit platelet activation.Considering the impact of polyphenols-rich diets on human platelet function, a recent critical review has to be considered with attention [Ostertag et al 2010]. This review summarized 25 well-controlled human intervention trials and revealed a wide heterogeneity between studies as for levels of polyphenol intake (18.6 mg to 2.20 g/ day), study population (healthy, increased risk factors and/or clinical disease), study size (between 6 and 1535 subjects), length of supplementation (acute intake for 1 day to chronic intake for over 90 days) and variety of tests used to assess platelet function.…”
mentioning
confidence: 99%
“…It is difficult to presume, from a relatively small number of well designed and controlled human trials, how polyphenols improve the cardio-vascular function or the glucose homeostasis (Ostertag et al 2010;Alexandru et al 2012). Clinical studies which investigate the potential role of polyphenols in health and disease are difficult to design, as long-term studies are interfered by the treatment and the evolution of the disease.…”
Section: Reply From D Margina and M Iliementioning
confidence: 99%
“…Still, even if authors state that additional larger, longerduration and extensive trials are required to confirm the exact mechanism of cardiovascular benefits comong from polyphenols and their effects on glucose homeostasis and adipose tissue, incorporating plant foods that are rich in flavanols in the diet of healthy individuals could help to reduce cardio-vascular risk (Ostertag et al 2010;Alexandru et al 2012). …”
Section: Reply From D Margina and M Iliementioning
confidence: 99%
“…Regarding prostate cancer, however, the results obtained by these researchers for this particular chromone analogue do not support a protective effect [30], which reflects selectivity, another relevant feature of the anticancer protective activity of this kind of systems. Additionally, dietary polyphenols were shown to possess beneficial cardiovascular effects [31,32].…”
Section: Chemoprevention Versus Chemother-apymentioning
confidence: 99%